2019
DOI: 10.1111/tmi.13276
|View full text |Cite
|
Sign up to set email alerts
|

Point of care ultrasound: does the presence of ascites in severe pre‐eclampsia correlate with poor maternal and neonatal outcome?

Abstract: objective Ascites in severe pre-eclampsia may impact foetal and maternal outcomes. The objective was to determine the prevalence of ascites in women with severe pre-eclampsia by point of care (POC) ultrasound and to determine whether it correlates with higher perinatal risks.methods Prospective cohort study of patients admitted with severe pre-eclampsia at 2 teaching hospitals in Kigali, Rwanda. Serial POC ultrasound was performed to document ascites. Patients were stratified by the presence of ascites in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…5 A second prospective cohort study showed an association between ascites and both maternal and perinatal outcomes such as premature obstetrics and low birthweight. 14 There is no clear etiology of ascites with PE, as well as no clear evidence for the management of PE associated with ascites. According to one report, early termination may improve the outcome in cases of preeclampsia associated with ascites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A second prospective cohort study showed an association between ascites and both maternal and perinatal outcomes such as premature obstetrics and low birthweight. 14 There is no clear etiology of ascites with PE, as well as no clear evidence for the management of PE associated with ascites. According to one report, early termination may improve the outcome in cases of preeclampsia associated with ascites.…”
Section: Discussionmentioning
confidence: 99%
“…One cohort study reported that ascites was associated with maternal events such as eclampsia, pulmonary edema, renal failure, and disseminated intravascular coagulation 5 . A second prospective cohort study showed an association between ascites and both maternal and perinatal outcomes such as premature obstetrics and low birthweight 14 …”
Section: Discussionmentioning
confidence: 99%
“…One cohort study reported that ascites was associated with maternal events such as eclampsia, pulmonary edema, renal failure, and disseminated intravascular coagulation 9) . A secondd prospective cohort study showed an association between ascites and both maternal and perinatal outcomes such as premature obstetrics and low birth weight 10) . Although both studies described patients diagnosed with severe PE, the case described here did not show severe hypertension nor any other related pathological features.…”
Section: Discussionmentioning
confidence: 99%
“…Ascites and/or pleural effusion have been detected clinically and on ultrasound in 10% to 21% and 44% to 54%, respectively, of women with PET-SF. [4][5][6][7] Woods et al 5 found that maternal ascites were associated with a sixfold increased risk of congestive cardiac failure and a ninefold increased risk of adult respiratory distress syndrome in women with HELLP syndrome. Guan et al 8 found that 52.6% of women with PET-SF and ascites developed cardiopulmonary dysfunction 5.1 ± 2.6 days following the diagnosis of ascites.…”
mentioning
confidence: 99%
“…A prospective cohort study of Rwandan women admitted with PET-SF found the presence of ascites on ultrasound was associated with earlier delivery, higher stillbirth rates, lower birth weight, higher rates of neonatal intensive care admission, and prolonged maternal hospital stay. 4 A matched cohort study found the presence of ascites with PET-SF was associated with an increased risk of a composite adverse maternal outcome of eclampsia, pulmonary oedema, AKI or disseminated intravascular coagulation (adjusted OR 16.4 (95% CI 2.9-93.3)). 6 A retrospective study of the expectant management of early-onset PET-SF found that the serum albumin and presence of ascites/pleural effusions were factors affecting prolongation of pregnancy.…”
mentioning
confidence: 99%